Recurrent respiratory papillomatosis: Analysis of the economic impact generated by surgical treatment - Lugo, Juan Antonio (2017)
Objective: To evaluate the economic impact generated by surgical treatment of recurrent respiratory papillomatosis in the tertiary care level. Recurrent respiratory papillomatosis is a prevalent entity. The economic impact it generates is mainly due to the need for repeated surgical interventions throughout its progression, in addition to the morbidity it causes to the patient. Materials and methods: This retrospective, observational, cross-sectional study was carried out at the Specialty Hospital No. 2, National Medical Center of the Northwest, Mexican Social Security Institute (IMSS), using a non-probability sampling by consecutive case series. In the general description of the study, clinical records of patients diagnosed with recurrent respiratory papillomatosis treated at this institution from January 2010 to January 2012 were reviewed. Data such as age, gender, surgical management and/or adjuvant therapy, and cost generated by exclusive surgical care, were collected. Results: Out of a total of 103 reviewed files, only 39 were complete and met the inclusion criteria: 16 (41%) were female and 23 (59%) were male. Twenty-seven (27) cases (69%) were juvenile patients and 12 (30.8%) were adults. Only 19 cases (48.7%) received adjuvant therapy. Tracheotomy was performed in 15 cases (38.5%). The direct cost for resection surgery was $322,943.92 (22,190 USD) in the juvenile group and $55,225.33 (3,790 USD) in the adult group. Conclusions: Surgical treatment for recurrent respiratory papillomatosis represents a financial burden and great morbidity for both health institutions and the family.